Attention Deficit and Academic Stress among High School Students - W, Joshy Renjen; Selvakumar, Y Stanly (Journal of Advanced Research in English & Education, 2022)
Attention deficit (AD) refers to a family of related chronic neurobiological disorders that get in the way with an individual’s ability to attend the responsibilities in developmentally appropriate ways. The symptoms of AD include incapacity to maintain attention and concentration, distractibility. Children with AD have functional mutilation across multiple settings including home, school , peer relationships. AD has also been shown to have long- term bad effects on academic performance, professional accomplishment , social-emotional growth. Children with AD experience an incapability to pay attention in class and the harmful consequences of such behavior. Contemporary life is full of problems, deadlines, frustrations and demands. For many adolescents, stress is so frequent and it has become a way of life. Stress is one of the blocks of academic performance of early adolescents. Taking into consideration this circumstances, the researcher felt a need to conduct a study to know about the AD and Academic Stress among High school students in relation to their sex, age, type of school, nature of school, father’s profession, mother’s profession, educational qualification of parents, accommodation, monthly income and survival of father and mother. How to cite this article:  Renjen WJ. Attention Deficit and Academic Stress among High School Students. J Adv Res Eng & Edu 2022; 7(1): 5-7